Study On Outcome of Different Combination of Dexamethasone, Hyaluronidase and Placental Extract for Treatment of Oral Submucous Fibrosis (KYAMC Journal, 2019)
Background: Oral submucous fibrosis is a chronic debilitating disease of the oral cavity characterized by inflammation and progressive fibrosis of the submucosal tissues. It is a precancerous condition of the oral mucosa characterized by excessive production of collagen leading to inelasticity of the oral mucosa and atrophic changes of the epithelium. A wide range of treatment including drug management, surgical therapy, and physiotherapy have been attempted till date, with varying degrees of benefit, but none have been able to cure this disease.Objectives: To evaluate the efficacy of Intralesional 'Dexamethasone Plus Hyaluronidase plus Placental extract in comparison to intralesional injections of 'Dexamethasone plus Hyaluronidase in the management of OSMF patients.Materials and Methods: Thirty patients with OSMF were randomly divided equally into two groups. Fifteen patients in 'Dexamethasone plus Hyaluronidase(Group-I)' group received biweekly intralesional injections of Dexamethasone (4mg/ml) plus Hyaluronidase 1500 IU in buccal mucosa for a period of 12 weeks. Other Fifteen patients in'Dexamethasone plus Hyaluronidase plus placental extract (Group-II)' group received biweekly intralesional injections of Dexamethasone (4mg/ml) plus Hyaluronidase 1500 IU plus placental extract in buccal mucosa for a period of 12 weeks. Parameters taken in the study were burning sensation, and mouth opening. Descriptive statistics, paired t test and unpaired t test were used for statistical analysis.Results: The pre- and post-treatment Differences were found to be statistically not significant for both the groups (p